Kisspeptin Exhibits Stimulatory Effects on Expression of the Genes for Kisspeptin Receptor, GnRH1 and GTH Subunits in a Gonadal Stage-Dependent Manner in the Grass Puffer, a Semilunar-Synchronized Spawner - Zahangir, Md. Mahiuddin; Shahjahan, Md.; Ando, Hironori (Frontiers in Endocrinology, 2022)
Kisspeptin has an important role in the regulation of reproduction by directly stimulating the secretion of gonadotropin-releasing hormone (GnRH) in mammals. In non-mammalian vertebrates, there are multiple kisspeptins (Kiss1 and Kiss2) and kisspeptin receptor types, and the two kisspeptins in teleosts have different effects depending on fish species and reproductive stages, serving reproductive and non-reproductive functions. In the grass puffer, Takifugu alboplumbeus, which has only a single pair of kiss2 and kissr2, both genes display seasonal, diurnal, and circadian oscillations in expression in association with the periodic changes in reproductive functions. To elucidate the role of kisspeptin in this species, homologous kisspeptin peptide (gpKiss2) was administered at different reproductive stages (immature, mature and regressed) and the expression levels of the genes that constitute hypothalamo-pituitary-gonadal axis were examined in male grass puffer. gpKiss2 significantly elevated the expression levels of kissr2 and gnrh1 in the brain and kissr2, fshb and lhb in the pituitary of the immature and mature fish. No noticeable effect was observed for kiss2, gnih, gnihr, gnrh2 and gnrh3 in the brain and gpa in the pituitary. In the regressed fish, gpKiss2 was ineffective in stimulating the expression of the gnrh1 and GTH subunit genes, while it stimulated and downregulated the kissr2 expression in the brain and pituitary, respectively. The present results indicate that Kiss2 has a stimulatory role in the expression of GnRH1/GTH subunit genes by upregulating the kissr2 expression in the brain and pituitary at both immature and mature stages, but this role is mostly ineffective at regressed stage in the grass puffer.